2003
DOI: 10.1063/1.1616654
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical emission characteristics of radio-frequency-driven hollow slot microplasmas operating in open air

Abstract: Articles you may be interested inCharacteristics of atmospheric-pressure, radio-frequency glow discharges operated with argon added ethanol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…At lowcurrent densities, the discharge current increases in proportion to the RF voltage across the electrode gap and the differential conductivity of the plasma is positive. This is similar to the mode in low-pressure glow discharges, and corresponds to the operation regime of most reported RF APGD experiments [1]- [7], [9], [16]. When the current density increases to a critical threshold, the discharge plasma evolves into a different operation regime in which the discharge current increases with decreasing gap voltage and the differential conductivity becomes negative [8].…”
Section: Current-voltage Characteristicsmentioning
confidence: 84%
“…At lowcurrent densities, the discharge current increases in proportion to the RF voltage across the electrode gap and the differential conductivity of the plasma is positive. This is similar to the mode in low-pressure glow discharges, and corresponds to the operation regime of most reported RF APGD experiments [1]- [7], [9], [16]. When the current density increases to a critical threshold, the discharge plasma evolves into a different operation regime in which the discharge current increases with decreasing gap voltage and the differential conductivity becomes negative [8].…”
Section: Current-voltage Characteristicsmentioning
confidence: 84%
“…10 So far, the issue of negative differential conductivity has been addressed with avoidance strategies by using, for example, high excitation frequencies 10 or small electrode gaps. 6,11,13 Given the direct link of differential conductivity to plasma stability, it is interesting to note that in Fig. 2 the applied voltage always increases with the discharge current density.…”
mentioning
confidence: 99%
“…In the past, dielectric insulation of electrodes has been widely believed to be necessary for APGD at kilohertz but not at megahertz. [4][5][6][7][8][9][10][11][12] Our study is based on a one-dimensional, self-consistent, and continuum model originally developed for rf APGD that has achieved excellent agreement with experimental data. 12 We consider rf DBD in atmospheric helium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Often this is realized in a jetlike configuration. [2][3][4][5][6][7][8][9][10][11] The vast majority of APGD jets reported so far employ sinusoidal excitation, although it has been known that nonsinusoidal excitation, through voltage pulsing, for example, offers a useful freedom to further improve APGD performance. 12 Initial results from few reported studies of pulsed APGD jets 4,10,13 have shown their general similarity to and contrast with sinusoidal APGD jets.…”
mentioning
confidence: 99%